DO trade and technology reduce asymmetries? Evidence from manufacturing industries in the EU - Riccardo Rovelli; Raffaele Paci (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1997)
Are asymmetric shocks to output less important for industries which are more open to trade and more technology-intensive? Our results, obtained from a correlation analysis between growth rates of value added in thirteen manufacturing industries in eleven European countries between 1979 and 1990, clearly support the hypothesis. This finding suggests that policies which promote trade and technological innovation may help to decrease the importance of the asymmetric components of the business cycle within European countries.
Keywords: 330